2014
DOI: 10.1007/s10897-014-9733-4
|View full text |Cite
|
Sign up to set email alerts
|

Making the Decision to Participate in Predictive Genetic Testing for Arrhythmogenic Right Ventricular Cardiomyopathy

Abstract: This paper describes the experience of predictive genetic testing for Arrhythmogenic Right Ventricular Cardiomyopathy in the context of novel gene discovery. Two approaches to making the decision to engage in genetic testing were apparent: the decision to be tested either (a) develops gradually over time or (b) happens so quickly that it is felt as a "fait accompli." Six key factors that influenced the particular approach taken by the participants were identified: (1) scientific process--available and relevant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 82 publications
(135 reference statements)
0
9
1
Order By: Relevance
“…Qualitative research has suggested that a family history of SCA/D is a motivator for individuals in pursuing both genetic testing and cardiac evaluation (Manuel and Brunger 2014;van der Werf et al 2014)]. This study did not find a significant association between family history of SCA/D and uptake of genetic testing, regardless of the relationship with the proband.…”
Section: Family History Of Sudden Cardiac Arrest/deathcontrasting
confidence: 56%
“…Qualitative research has suggested that a family history of SCA/D is a motivator for individuals in pursuing both genetic testing and cardiac evaluation (Manuel and Brunger 2014;van der Werf et al 2014)]. This study did not find a significant association between family history of SCA/D and uptake of genetic testing, regardless of the relationship with the proband.…”
Section: Family History Of Sudden Cardiac Arrest/deathcontrasting
confidence: 56%
“…This reflected a specific other-oriented approach to responsibility for women, which was often implied by their familial position. A good formulation of this kind of affective/relational GR was expressed in a study by Manuel and Brunger (2014) on GT for ARVC " […] relational responsibility reinforces that individual choices are socially embedded within the nexus of our social relationships and the meanings that we assign to these interactions. It also reaffirms that decisions about genetic testing do not happen in silo but are discussed amongst family members, particularly between spouses" (p. 1050).…”
Section: Gr Of At-risk People In the Context Of The Family (B)mentioning
confidence: 99%
“…Some studies considered familial roles other than that of women managing health in the family, such as those of male partners and fathers (Hallowell et al, 2006) or those of parents toward children (Forrest et al, 2003;Arribas-Ayllon et al, 2008b;Manuel and Brunger, 2014;Vavolizza et al, 2015) or of adults toward distant relatives (Etchegary and Fowler, 2008;Etchegary et al, 2009).…”
Section: Disclosure (B2)mentioning
confidence: 99%
“…In the NL TMEM43 p.S358L population, ICD therapy has significantly improved the survival of affected individuals and is an essential prophylactic (diagnosis based on positive mutation status alone) first-line treatment for males. 11 A small number of qualitative studies with ARVC families segregating the TMEM43 p.S358L mutation 12 and other cardiomyopathies [13][14][15] highlight general psychosocial burdens for at-risk families. Experiential knowledge of loss and death was clear, 12 while interviews with individuals tested for HCM or Long QT syndrome revealed parents' concern about their children's futures.…”
Section: Introductionmentioning
confidence: 99%
“…11 A small number of qualitative studies with ARVC families segregating the TMEM43 p.S358L mutation 12 and other cardiomyopathies [13][14][15] highlight general psychosocial burdens for at-risk families. Experiential knowledge of loss and death was clear, 12 while interviews with individuals tested for HCM or Long QT syndrome revealed parents' concern about their children's futures. 13,14 Relatives of young SCD victims in the Netherlands described ongoing worry and a desire to prevent a subsequent fatal event in remaining children and grandchildren.…”
Section: Introductionmentioning
confidence: 99%